Pidana Tabrak Lari Tragis: Tinjauan Hukum Kontemporer - Fahhrani Cakra Karinaputri; Hendra Suherman; Deaf Wahyuni Ramadhani (Jurnal Litigasi Amsir, 2025)
A traffic accident involves vehicles on the road that can cause material loss, injury or even death. This accident can occur due to various factors. The focus of the problem in this research is: What is the criminal responsibility for hit-and-run perpetrators based on laws and regulations in Indonesia, what are the factors that cause accidents? This type of research is normative juridical where the data source used is secondary data consisting of primary legal materials, secondary legal materials and tertiary materials. The data collection technique was carried out by document study. Indonesia is a country of law, the Criminal Code, by Pasal 235 ayat (1) Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas Jalan dan Angkutan Jalan